CHILDHOOD FEARS PROBLEM IN WORKS OF NATIONAL AND INTERNATIONAL RESEARCHERS - Kaminska, Olga; Hromyk, Nataliia (PSYCHOLOGICAL JOURNAL, 2018)
It was emphasized that the relevance of the study has been caused by its major role in child’s life. The fear might exist on a conscious level of personality as well as on a subconscious one having impact on all aspects of life. When the fear becomes a phobia it is able to decrease the quantity of an individual’s life, bounds one’s vital activity and social cooperation, negatively affects socialization development, which is very important in a preschool age. Accordingly, the fear actualization, its compulsive nature, disturbs the child’s personality formation process, causes destructive changes in the communication with adults and children of the same age. It also may cause a misperception of substantive environment depending on the object of fear. Theoretical analysis of “fear” conception has been accomplished; its nature has been determined by different approaches in psychology. The views of national and international scientists regarding the fear problem have been presented. Scientists’ points of view on the fear and anxiety differentiation have been enlightened. The place of “fear” conception in psychological categories has been determined. Special aspects of fear origin among the children of preschool age have been analyzed. Most common kinds of fear among children have been determined as well as the stages of their transitions into phobias. The influence of child’s surrounding community on the creation of obsessive fears has been displayed. Ways and forms of preschool age children’s fear correction have been pointed. The psychological defense mechanisms’ role in a leveling of child’s own fears has been discovered. The necessity of psychological support service for children who struggle from obsessive fears and phobias have been brought into focus. It is discovered that the fear is determined as a reaction to the specific outer menace, instinct, a fundamental emotion, a mental state, an elaborated anxiety and danger signal. The fear is always directed toward the object and the anxiety might appear regardless of the motive. The anxiety is a reaction to imaginary, non-existent danger, but the fear – on a contrary – is a reaction to concrete one. As a compound structure, the fear itself includes physiological, behavioral and cognitive aspects and can be determined as a negative emotional state, which is connected to the reflection of a certain danger for individual’s life and prosperity in consciousness. It appears in anticipation and prediction of a danger. It is underlined that the preschool age is a sensitive period for fear uprising, which can take on vary types and forms. It includes psychological defense mechanisms switching-on such as runaway and denial which are widespread among the children of this age. It is proved that the corrective work, which is focused on actualized fears overcoming, provides for the use of psychological support not only for a child, but for immediate environment also. Key words: fear, phobia, anxiety, emotions, preschool age.